Diabetes mellitus, chronic pancreatitis and primary hyperparathyroidism: is there a connection? - Anna M. Gorbacheva (Endocrinology Research Centre, 2019)
Hyperparathyroidism is a relatively frequent condition characterized by hypersecretion of parathyroid hormone. There are several forms of primary hyperparathyroidism. Each form affects its target region. In the visceral form, nephrocalcinosis, nephrolithiasis and peptic and duodenal ulcers are common. The pancreas is also a target organ. This article describes a clinical case of a patient with diabetes mellitus and previously treated primary hyperparathyroidism. The patient was admitted to the hospital due to poor glycaemic control. During the hospitalization, diabetes mellitus developed as a consequence of frequent relapses of chronic pancreatitis (outcome of the visceral form of primary hyperparathyroidism and severe hypertriglyceridemia). Glycaemic control was achieved after treatment of acute pancreatitis and insulin administration. This clinical case is an example of the impact of previous primary hyperparathyroidism (even after radical treatment and remission) on the development of a multi-faceted comorbidity.